Exploring the narrative landscape: The discursive construction of identity for Chinese enterprises in Africa - Wenyu Liu; Yu Yang (PLoS ONE, 2025)
This study investigates the construction of corporate identities by Chinese enterprises in Africa, employing the Three-dimensional Model of Fairchough in conjunction with the corporate communication strategies outlined by Kim and Rader. Through an extensive analysis of official website content from 200 Chinese companies, this study explores how these corporations utilize communication strategies to project their identities. The findings reveal a strategic use of discourse to align corporate practices with local cultures and business norms, facilitating their expansion and acceptance in African markets. This study contributes to understanding the dynamic and constructed nature of corporate identities in cross-cultural settings and provides insights into the strategic communication practices of Chinese firms in Africa.